Ungendering and Regendering Shelters for Survivors of Human Trafficking - Hacker, Daphna (Social Inclusion, 2015)
This article is based on intensive fieldwork in the two Israeli shelters designated for victims of human trafficking and slavery. The shelters, one for women and one for men, are a refuge for survivors of sex trafficking; labor migrants subjected to severe exploitation by their employers; and asylum seekers who arrived in Israel after experiencing severe physical and emotional abuse at the hands of kidnappers and smugglers en route to Israel. The study included interviews with policy makers and professionals, and with women and men who resided at the shelters, as well as an analysis of the relevant legislation and official reports. The article explores the problematic gendered differentiations between the two shelters. Most significantly, while support for residents of the shelter for women is anchored by emotional and psychological rehabilitation, residents of the shelter for men do not receive any therapeutic support. At the same time, while staff in the shelter for men put significant effort into the reintegration of the men into the labor force, the women’s employment prospects receive less attention. Based on these and other findings, the article cautions against gender-biased rehabilitation services for victims of human trafficking and slavery, and calls for a gender-sensitive rehabilitation theory and practice.